Case proven: exercise associated hyponatraemia is due to overdrinking. So why did it take 20 years before the original evidence was accepted? - Noakes, T. D.; Speedy, D. B. (British Journal of Sports Medicine, 2006)
The reluctance to accept the evidence may be because it conflicted with the prevalent message of the sports drink industry.